Recognition of Sulfonylurea Receptor (ABCC8/9) Ligands by the Multidrug Resistance Transporter P-glycoprotein (ABCB1): FUNCTIONAL SIMILARITIES BASED ON COMMON STRUCTURAL FEATURES BETWEEN TWO MULTISPECIFIC ABC PROTEINS - Bessadok, Anis (American Society for Biochemistry and Molecular Biology, 2011)
ATP-sensitive K(+) (K(ATP)) channels are the target of a number of pharmacological agents, blockers like hypoglycemic sulfonylureas and openers like the hypotensive cromakalim and diazoxide. These agents act on the channel regulatory subunit, the sulfonylurea receptor (SUR), which is an ABC protein with homologies to P-glycoprotein (P-gp). P-gp is a multidrug transporter expressed in tumor cells and in some healthy tissues. Because these two ABC proteins both exhibit multispecific recognition properties, we have tested whether SUR ligands could be substrates of P-gp. Interaction with P-gp was assayed by monitoring ATPase activity of P-gp-enriched vesicles. The blockers glibenclamide, tolbutamide, and meglitinide increased ATPase activity, with a rank order of potencies that correlated with their capacity to block K(ATP) channels. P-gp ATPase activity was also increased by the openers SR47063 (a cromakalim analog), P1075 (a pinacidil analog), and diazoxide. Thus, these molecules bind to P-gp (although with lower affinities than for SUR) and are possibly transported by P-gp. Competition experiments among these molecules as well as with typical P-gp substrates revealed a structural similarity between drug binding domains in the two proteins. To rationalize the observed data, we addressed the molecular features of these proteins and compared structural models, computerized by homology from the recently solved structures of murine P-gp and bacterial ABC transporters MsbA and Sav1866. Considering the various residues experimentally assigned to be involved in drug binding, we uncovered several hot spots, which organized spatially in two main binding domains, selective for SR47063 and for glibenclamide, in matching regions of both P-gp and SUR.